Plasma 25‐hydroxyvitamin D and the risk of breast cancer in the European prospective investigation into cancer and nutrition: A nested case–control study. Issue 7 (22nd April 2013) - Kühn, Tilman; Kaaks, Rudolf; Becker, Susen; Eomois, Piia‐Piret; Clavel‐Chapelon, Françoise; Kvaskoff, Marina; Dossus, Laure; Tjønneland, Anne; Olsen, Anja; Overvad, Kim; Chang‐Claude, Jenny; Lukanova, Annekatrin; et al.
Abstract : Experimental evidence suggests that vitamin D might play a role in the development of breast cancer. Although the results of case–control studies indicate that circulating 25‐hydroxyvitamin D [25(OH)D] is inversely associated with the risk of breast cancer, the results of prospective studies are inconsistent. A case–control study embedded in the European Prospective Investigation into Cancer and Nutrition (EPIC) was carried out comprising 1, 391 incident breast cancer cases and 1, 391 controls. Multivariable conditional logistic regression models did not reveal a significant overall association between season‐standardized 25(OH)D levels and the risk of breast cancer (ORQ4–Q1 [95% CI]: 1.07 [0.85–1.36], p trend = 0.67). Moreover, 25(OH)D levels were not related to the risks of estrogen receptor positive tumors (ORQ4–Q1 [95% CI]: 0.97 [0.67–1.38], p trend = 0.90) and estrogen receptor negative tumors (ORQ4–Q1 [95% CI]: 0.97 [0.66–1.42], p trend = 0.98). In hormone replacement therapy (HRT) users, 25(OH)D was significantly inversely associated with incident breast cancer (ORlog2 [95% CI]: 0.62 [0.42–0.90], p = 0.01), whereas no significant association was found in HRT nonusers (ORlog2 [95% CI]: 1.14 [0.80–1.62], p = 0.48). Further, a nonsignificant inverse association was found in women with body mass indices (BMI) < 25 kg/m 2 (ORlog2 [95% CI]: 0.83 [0.67–1.03], p = 0.09), as opposed to a borderline significant positive association in women with BMI ≥ 25 kg/m 2 (ORlog2 [95% CI]: 1.30 [1.0–1.69], p = 0.05). Overall, prediagnostic levels of circulating 25(OH)D were not related to the risk of breast cancer in the EPIC study. This result is in line with findings in the majority of prospective studies and does not support a role of vitamin D in the development of breast cancer. Abstract : What's new? Experimental studies have indicated that vitamin D may play a role in preventing tumor formation in the breast. However, in the present investigation, the largest prospective case‐control study on circulating 25‐hydroxyvitamin D (25(OH)D) and breast cancer risk conducted to date, pre‐diagnostic levels of 25(OH)D were found to be unrelated to overall breast cancer risk. While the results support those of similar prospective studies, a significant inverse association was detected between 25(OH)D levels and incident breast cancer in women taking hormone replacement therapy, suggesting that background factors may influence risk associations.